IMPROVING STUDENT’S VOCABULARY MASTERY USING ANIMATION VIDEO - Weangga Apriliani Utami; Syarifuddin Dollah; Syarifah Faradiba (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This research aims to determine the development of students' vocabulary mastery through English animation videos. The method used in this research was quantitative with a pre-experimental research design with a sample of 33 students XI IPS 1 using cluster random sampling technique. In obtaining the data, the researcher used the test as an instrument. The results of the data analysis showed that by using English animation video media, the student’s vocabulary mastery developed. It can be proven by the t-test value was lower than P (0.000 ˂ 0.05) which means (H0) of this research was rejected and (H1) was accepted. Therefore, it is concluded that English animation videos develop the vocabulary mastery of the eleventh-grade students of SMA Negeri 3 Sidrap. Keywords: Vocabulary, English animation video